Memaknai Pesan Islam: Studi Fenomenologi Mualaf di Purwokerto - Rokhis, Rokhis (International Conference of Moslem Society, 2016)
The phenomenon of a person to change religions is an interesting thing to be studied more in depth. However, the decision to convert is not a trivial thing, and should be considered carefully. The refusal of parents, friends, business colleagues and others is a challenge that must be faced when a person chooses to convert. Nevertheless, the existence of a spiritual experiences are experienced, makes faith grow stronger to convert. In other words, a person attempts to move this religion has its own meaning and appreciation for such individuals. This study intends to study forms of experience from the perspective of a new convert to Islam (convert), or in other words can be defined as the study of meaning, where meaning is broader than just the language they represent. Thus, in this study the authors attempted menggungkap deepest essence or meaning of the experiences of the subject.